Interfacial interactions and structures of imidazolium-based ionic liquids on black phosphorus surface from first-principles - Lu, Yunxiang; Hong, Yumei; Xu, Zhijian; Liu, Honglai (Journal of molecular liquids, 2021)
•The interaction between imidazolium-based ILs and the BP surface was studied via first-principles calculations.•The adsorption of ILs on BP is governed by the interplay of strong electrostatic interactions and weak vdW forces.•The alkyl chain length in the cation acts as a significant role in tuning the adsorption behaviors.•The differences of adsorption features between protic ILs and aprotic ILs were unraveled. The interphase between ionic liquids (ILs) and electrode material surfaces has been the subject of numerous experimental and theoretical studies, because ILs show great potential as electrolytes in electrochemical devices such as batteries and capacitors. However, the interface of ILs and black phosphorus (BP), a promising electrode material for next-generation energy storage devices, has not been studied in detail so far. In this work, interfacial interactions and structures of a series of imidazolium-based ILs on the BP surface were systematically investigated using first-principles calculations. The adsorption of these ILs on BP is dominated by the interplay of strong electrostatic interactions between the adsorbed ions and weak van der Waals forces between the ILs and the substrate accompanied by HB and aromatic π interactions. The length of the alkyl chains in the cation acts as a significant role in tuning the adsorption behaviors with respect to surface affinity, packing restriction, and charge localization. In addition, the adsorption differences between protic ILs and aprotic ILs were also examined.